PENGARUH PERMAINAN FUTSAL TERHADAP PENINGKATAN KEBUGARAN JASMANI PADA SISWA EKSTRAKURIKULER SMP NEGERI 4 RAJADESA - Dadi Lukmanul Jauhari; Dadan Muldan (STKIP Subang, 2025)
This study aims to determine the effect of futsal games on improving the physical fitness of extracurricular students at SMP Negeri 4 Rajadesa in 2025. The research method used was a quasi-experimental design with a pre-test post-test group design. The sample consisted of 20 students participating in futsal extracurricular activities. Physical fitness tests included a 60-meter sprint, sit-ups, pull-ups, vertical jumps, and a 1200-meter run. Data were analyzed using a paired sample t-test with SPSS. The results showed significant improvements in all components of physical fitness after students followed a structured futsal training program for six weeks. Thus, futsal can be considered an effective extracurricular activity to enhance students’ physical fitness.